Short-term effects of the allelochemical umbelliferone on Triticum durum L. metabolism through GC-MS based untargeted metabolomics - Misra, Biswapriya B (Plant science : an international journal of experimental plant biology, 2020)
Copyright © 2020 Elsevier B.V. All rights reserved.